ASSESSMENT AND EVALUATION METHODS AS TOOLS FOR MEASURING STUDENTS’ KNOWLEDGE, SKILLS AND CRITICAL THINKING ABILITIES - BEHRUZ SALOHIDDINOV VAHOBIDDIN O‘G‘LI (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT Assessment and evaluation are essential components of the educational process, serving as instruments to measure students’ academic achievement, skill development, and critical thinking capabilities. Effective assessment methods provide educators with valuable insights into learners’ strengths, weaknesses, and areas requiring improvement, thereby guiding instructional strategies and curriculum design. This study explores various assessment techniques, including formative and summative evaluations, standardized testing, performance-based assessments, and self-assessment approaches, emphasizing their role in fostering analytical thinking and problem- solving skills.